Ecological characterization of cold-seep epifauna in the South China Sea. (September 2020) - Zhao, Yu; Xu, Ting; Law, Yu Sheung; Feng, Dong; Li, Niu; Xin, Renjie; Wang, Hu; Ji, Fuwu; Zhou, Huaiyang; Qiu, Jian-Wen
Abstract: Site F, an active cold seep situated on the northeastern continental slope of the South China Sea (SCS), has not been systematically surveyed since its first discovery in 2007. Here we report the results of a ROV transect survey of this cold seep conducted in 2018, which mapped the distribution of the substrates and quantified epifauna along parallel dive tracks. The site, measuring 180 m × 180 m, is characterized by a central part of authigenic carbonate outcrops with crevices releasing gas bubbles, which support high densities of bathymodiolin mussels Gigantidas platifrons (up to 273 individuals m −2 ) and galatheid squat lobsters Shinkaia crosnieri (up to 300 individuals m −2 ). On more condensed carbonate crusts, G. platifrons and the munidopsid squat lobsters Munidopsis spp. are present at low densities. The outskirts of the site are dominated by soft sediment, with bacterial mats and sparsely distributed G. platifrons and their shells, as well as the vestimentiferan tubeworm Paraescarpia echinospica . Sampling in various locations of the cold seep yields 10 new records of epibenthic animals as determined by watching the captured videos, morphological analysis as well as sequencing the COI and 16S rRNA gene sequences. Stable isotope analysis showed that biogenic methane is the main carbon source for most of the macrobenthos in this community. Many of these SCS cold seep macrobenthos have been reported from hydrothermal vents of the Okinawa Trough, indicating high connectivity between the two chemosynthesis-based communities in the Western Pacific. Graphical abstract: Image 1 Highlights: We conducted an ecological survey of a cold seep in the South China Sea. This community is dominated by deep-sea mussels and squat lobsters. Molecular analyses revealed new records of epifauna on rocks. This community is very similar with vent communities in the Okinawa Trough. Stable isotope analyses revealed the food-web structure.